Prevalence and variables associated with depression, anxiety, and stress among Chilean higher education students, post-pandemic - Martínez-Líbano, Jonathan; Torres-Vallejos, Javier; Oyanedel, Juan C.; González-Campusano, Nicol; Calderón-Herrera, Gilda; Yeomans-Cabrera, María-Mercedes (Frontiers in Psychiatry, 2023)
Objective: The present study aimed to determine the prevalence and variables influencing depression, anxiety, and stress in Chilean university students. Method: A representative sample (n = 1,062) of Chilean university students and a cross-sectional study design were used. Bivariate analysis and multiple logistic regression were performed to identify risk factors associated with symptomatology. They were analyzed using descriptive statistics. A questionnaire with sociodemographic variables was applied in November 2022, in addition to the depression anxiety stress scale (DASS-21), instruments with excellent reliability in this population (α = .955; ω = .956). On the other hand, the Questionnaire of Problematic Alcohol and Drug Consumption (DEP-ADO) was applied. A descriptive analysis was performed, followed by bivariate analysis and multiple logistic regression using SPSS version 25. The variables showed a p-value < 0.05; they were declared statistically significant in the final model. Odds ratios (OR) were adjusted to a 95% confidence interval (95% CI), which was used to determine the independent predictors. Results: The prevalence of mental health problems in this population was high, with depressive symptoms in 63.1% of the sample; 69.2% with anxiety; 57% with stress; 27.4% with problematic alcohol consumption; 14.9% with inappropriate marijuana consumption. Some 10.1% of the sample reported daily medication with antidepressants and/or anxiolytics. Concerning significant variables for depression, these were: being female, belonging to sexual, not having children, having problematic marijuana use, and using prescription drugs. Concerning anxiety, the significant variables were being a woman, belonging to sexual minorities, being an adolescent, and consuming prescription medication. Finally, concerning stress, the significant variables were being a woman, belonging to sexual minorities, being a student dedicated exclusively to academic activities, and taking prescription medication. Conclusion: Chilean university students presented a high prevalence of anxiety, depression, and stress, where being female and belonging to sexual minorities seem to be the variables that have the greatest impact on susceptibility to mental health problems. These results should call the attention of political and university authorities in Chile to improve this population's mental health and quality of life since they are the following professional generation of our country.